Design Thinking in Policymaking Processes: Opportunities and Challenges. Issue 3 (22nd July 2016) - Mintrom, Michael; Luetjens, Joannah
Abstract : Design thinking has the potential to improve problem definition and mechanism design in policymaking processes. By promoting greater understanding of how citizens experience government services, design thinking can support public managers who desire to enhance public value. In Australia, as elsewhere, design thinking currently remains separated from mainstream policymaking efforts. This article clarifies the essence of design thinking and its applicability to policy development. Five design thinking strategies are discussed, all of which have lengthy histories as social science methodologies. They are (1) environmental scanning, (2) participant observation, (3) open‐to‐learning conversations, (4) mapping, and (5) sensemaking. Recent examples from Australia and New Zealand are used to illustrate how these strategies have been incorporated into policymaking efforts. The article concludes by considering how design thinking might be more broadly applied in policymaking, and the training and resourcing requirements that would entail. Abstract : Design thinking has the potential to improve problem definition, mechanism design, and implementation in policymaking. This article introduces five design thinking strategies and discusses how they might be integrated with traditional approaches to policy development.